2000
DOI: 10.1016/s0029-7844(00)01082-6
|View full text |Cite
|
Sign up to set email alerts
|

Complications of interval laparoscopic tubal sterilization: findings from the United States collaborative review of sterilization

Abstract: Interval laparoscopic sterilization generally is a safe procedure; serious morbidity is rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 4 publications
0
41
0
8
Order By: Relevance
“…A prospective, multi-centre cohort study in the United States found an overall complication rate of 0.9 per 100 procedures [19]. However, there were several key differences between the two studies, most notably that the U.S.-based study took place in a hospital setting, measured different types of complications at different points in time, and did not count 'failure to complete the procedure' as a complication (which is the main adverse event observed in our study).…”
Section: Discussionmentioning
confidence: 99%
“…A prospective, multi-centre cohort study in the United States found an overall complication rate of 0.9 per 100 procedures [19]. However, there were several key differences between the two studies, most notably that the U.S.-based study took place in a hospital setting, measured different types of complications at different points in time, and did not count 'failure to complete the procedure' as a complication (which is the main adverse event observed in our study).…”
Section: Discussionmentioning
confidence: 99%
“…This study followed more than 10,000 sterilized women for up to 14 years to assess safety, effectiveness and other sequelae such as regret, sexual function, menstrual abnormalities and future risk of hysterectomy. Overall, CREST found that female sterilization was safe with low rates of intraoperative and postoperative complications [41]. Furthermore, there was no evidence of increased risk of later sequelae such as menstrual abnormalities or adverse effects on sexual function [42,43].…”
Section: What Are the Long-term Effectiveness And Safety Of And Patimentioning
confidence: 92%
“…When complications occur they are most commonly haemorrhage from the fallopian tube or the mesosalpinx, and they rate from 0,1 to 4,6 % . [3][4][5][6][7]. The occurrence of major complications (0,6 % ) like vascular injury, bowel perforation 35 or damage to the genitourinary tract is really rare.…”
Section: Tubal Ligationmentioning
confidence: 99%